Sociolinguistic approach to primary school teachers' perceptions regarding the Issue of bilingual education in Moore-speaking rreas of Burkina Faso: the case of Ouagadougou and Tikare - (:unkn) unknown (My University, 2016)
This work, based on a sociolinguistic approach to primary school teachers' representations regarding the issue of bilingual education in Burkina Faso, is a doctoral thesis in sociolinguistics presented under the supervision of Professor Abou Napon. The identified problem is that education in Francophone Africa, particularly in Burkina Faso, faces a systemic crisis, exacerbated by the mismatch between the language of instruction (French) and the mother tongues of students in a multilingual context. The researcher's objective is to study teachers' representations concerning bilingual education to contribute to a language policy that integrates national languages. The methodology involved the collection of a significant oral corpus by gathering epilinguistic discourses of teachers in both urban and rural areas to better understand their perceptions of bilingual education. The thesis falls within the dynamics of contact sociolinguistics, employing a discursive approach to interactions in context, aiming to propose didactic solutions adapted to the multilingual African context. The analysis emphasizes the necessity of integrating learners' mother tongues and culture into education to improve students' learning and success. Other questions raised include the difficulty of choosing an African language of instruction (among the approximately sixty languages in the country) alongside French. This didactic perspective implies the need for an educational reform that includes national languages to address the challenges of an educational system still marked by pedagogy and didactic practices that overlook the sociocultural realities of learners.
Keywords: African Research